الهندسة الاجتماعیة وشبکات التواصل الاجتماعى وتأثیرها على المجتمع العربى - د. مها أحمد ابراهیم محمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aims at recognizing to extreme the Arab community isaware of how to protect their personal accounts and ways of penetration(hacking) of privacy on general level and focusing on social engineering onparticular. In addition to other available ways of training of the digital citizen. Theconcept of social engineering (the art of penetrating minds), the significance of ofsocial networks in the Arab world, and the importance of privacy from the point ofview of social networks’ users in the Arab world, as well as recognizing ways ofsocial networks penetration and ways of social engineering protection . So wecan point out that the Arab community awareness of social engineering is one ofits priorities for protecting their accounts in all social networks and the requiredskills to prevent attacks of this social engineering in all social networks.A sample of 336 individuals was applied to the current study. The studyalso comes up with the following results: positively, individuals of the academiccommunity succeeded at protecting their personal data automatically and at ahigh rate. Selection of fake names constitutes half of the academic community (53.2%), who use social networks and this is explored by their deny of personaldata or by writing fake personal data. In addition to hacking their bankingaccounts since 6.8% of the individuals were slightly hacked. One of the mostcommon methods of social engineering attacks are spam messages sent by afriend as congratulations (77.1%), followed by 53.2% who are convinced by thesignificance of programs to be downloaded, the importance of social networks inthe Arab world, the importance of privacy from users’ point of view of socialnetworks in the Arab world, as well as the identification of penetrate ways of thesocial networks and how to be protected from social engineering.